“I’m Not a Musician, But…”: Negotiating the Research Process in Examining the Lives of Musicians - Ramirez, Michael (Qualitative Sociology Review, 2014)
Identity politics have been of considerable interest to the qualitative research tradition as researchers have speculated on the extent to which identity and positionality matter in the field. In this autoethnography, I analyze private writings I composed while studying musicians’ life course trajectories in musical careers, paying particular attention to the methodological implications of my fieldwork decisions. I concentrate on: 1) issues of access, 2) identity politics, and 3) the ethics of relationships in the field. I analyze the extent to which I negotiated several (sometimes conflicting) ways I presented my identity in different settings and among different populations. My presentation of self-strategies – sometimes intentional, other times haphazard – allowed me successful entrée to the music world, though I remained an outsider within. I conclude with methodological implications highlighting the ways researchers’ identities may influence the research process and suggestions for qualitative researchers to consider in future studies.